Hybrid artificial intelligent systems : 11th International Conference, HAIS 2016, Seville, Spain, April 18-20, 2016, proceedings /: 11th International Conference, HAIS 2016, Seville, Spain, April 18-20, 2016, proceedings. ([2016]) - Unknown
No abstract available